Nasal Microbiota as a Potential Therapeutic Target for Allergic Rhinitis: An Emerging Perspective - Liang, Bing-Yu; Yang, Yi-Pin; Pan, Chun-Ya; Li, Fen-Fen; Zhou, Ping-Ting; Fu, Zi-Yue; Han, Yan-Xun; Wang, Qin; Pan, Hai-Feng; Liu, Yu-Chen (Current Pharmaceutical Design, 2025)
Allergic Rhinitis (AR) represents a significant global health challenge with extensive prevalence and profound impacts, necessitating the development of novel therapeutic approaches beyond conventional symptomatic treatment. Emerging research has elucidated the crucial role of nasal microbiota dysbiosis in both the pathogenesis and progression of AR. Although the dominant microbial phyla remain largely consistent, significant changes in microbial abundance, composition, and diversity are often observed. In addition, studies have shown a correlation between changes in nasal microbiota and immune markers such as immunoglobulin E levels, suggesting that microbiota changes can reflect the severity of AR. Therefore, targeted modulation of the aberrant nasal microbiota may offer a promising therapeutic approach for this disease. However, further research is crucial for elucidating the causal relationships between specific microbial characteristics, disease severity, and potential comorbidities. This article summarizes recent studies examining the pathogenic role of nasal microbiota dysbiosis, the differential microbial composition across nasal mucosal sites, and potential therapeutic targets in AR. The ultimate goal is to develop precision medicine-based therapeutic interventions that target the underlying pathophysiological mechanisms of AR through specific modulation of dysbiotic nasal microbiota, thereby potentially preventing disease progression and reducing the risk of associated comorbidities.
Keywords: allergic reaction